2018
DOI: 10.1039/c8an00136g
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced DNA detection using a multiple pulse pumping scheme with time-gating (MPPTG)

Abstract: Fluorescence signal enhancement induced by the binding of intercalators to DNA has been broadly utilized in various DNA detection methods. In most instances the increase in fluorescence intensity is associated with a concomitant increase of fluorescence lifetime. This increase of the fluorescence lifetime presents an additional opportunity to increase detection sensitivity. In this paper, we present a new approach to significantly enhance the sensitivity in detecting minute DNA concentrations. The approach is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Recently, we also realized that long-lived probes offer the possibility for multipulsed excitation, further improving the relative signal of fluorophores that present longer fluorescence lifetimes. , The highly enhanced signal by multipulsed excitation makes it feasible to utilize typically low brightness yet long-lived probes. Using such technology with time-gated detection, we demonstrated that the detection sensitivity could be enhanced by two orders of magnitude when using one of the earliest used DNA intercalators, ethidium bromide (EtBr). , Additional emission spectra decomposition allowed subtraction of the Raman contribution, further improving detection sensitivity …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we also realized that long-lived probes offer the possibility for multipulsed excitation, further improving the relative signal of fluorophores that present longer fluorescence lifetimes. , The highly enhanced signal by multipulsed excitation makes it feasible to utilize typically low brightness yet long-lived probes. Using such technology with time-gated detection, we demonstrated that the detection sensitivity could be enhanced by two orders of magnitude when using one of the earliest used DNA intercalators, ethidium bromide (EtBr). , Additional emission spectra decomposition allowed subtraction of the Raman contribution, further improving detection sensitivity …”
Section: Introductionmentioning
confidence: 99%
“…The fluorescence lifetime of DAPI is ∼2 ns, much shorter than the fluorescence lifetime of EtBr bound to DNA (∼20 ns). The long fluorescence lifetime of DNA-bound EtBr allows using time-gating for detection. , With such an approach, detection and visualization of less than 100 picograms of DNA in microliters of solution without any sample purification and DNA amplification were achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the majority of typical fluorophores, the fluorescence lifetime will range from sub-nanoseconds to a few nanoseconds, and only a handful of emitters will have a longer fluorescence lifetime. Long-lifetime emitters may have lifetimes in the range of 20 ns like ADOTA 5,6 or ethidium bromide when intercalated to DNA, 7,8 to hundreds of nanoseconds and microseconds like ruthenium metal–ligand complexes 912 (MLCs) and some metal clusters, 13,14 or even milliseconds with lanthanide-based emitters. 1518 Some quantum dot-type emitters will also have long emissive lifetimes over 20 ns.…”
Section: Introductionmentioning
confidence: 99%
“…When using multipulse pumping and time-gated detection (MPPTGD), even for relatively short probe lifetimes in the range of 20 ns, we increased the detection sensitivity by two orders of magnitude. 7,38…”
Section: Introductionmentioning
confidence: 99%